Job Satisfaction Mediation: The Influence of Organizational Culture on Employee Performance - Salehuddin; Siti Layyinatul Adabiyah; Arik Purwanto; Untung Wredhi Lestari; Nurul Qomariah (www.amertainstitute.com, 2024)
The development of the hospital industry in Jember Regency in 2024 experienced a significant increase. There are 14 types of hospitals with various types of hospitals. This causes competition in getting patients to also increase. The purpose of this study was to analyze the impact of organizational culture on employee performance with job satisfaction as an intervening variable at XYZ Hospital in Jember. The study population was all employees of XYZ Hospital totaling 420 employees. With the Isaac method and using a significance level of 1% of the population of 420, the sample required was 257 respondents (rounded to 260 respondents). Descriptive and inductive statistical analysis was carried out in obtaining research objectives. Organizational culture has a positive and significant effect on job satisfaction, but not significant on employee performance. Job satisfaction has a positive and significant impact on employee performance. Organizational culture has a positive and significant effect on employee performance through job satisfaction of employees at XYZ Hospital in Jember Regency.